Fruit and vegetable consumption in a sample of 11-year-old children in ten European countries - the PRO GREENS cross-sectional survey - Lynch, C. (2014)
Objective: To describe fruit and vegetable intake of 11-year-old children in ten European countries and compare it with current dietary guidelines. Design: Cross-sectional survey. Intake was assessed using a previously validated questionnaire containing a pre-coded 24 h recall and an FFQ which were completed in the classroom. Portion sizes were calculated using a standardized protocol. Setting: Surveys were performed in schools regionally selected in eight countries and nationally representative in two countries. Subjects: A total of 8158 children from 236 schools across Europe participating in the PRO GREENS project. Results: The total mean consumption of fruit and vegetables was between 220 and 345 g/d in the ten participating countries. Mean intakes did not reach the WHO population goal of >= 400 g/d in any of the participating countries. Girls had a significantly higher intake of total fruit and vegetables than boys in five of the countries (Sweden, Finland, Iceland, Bulgaria and Slovenia). Mean total fruit intake ranged between 114 and 240 g/d and vegetable intake between 73 and 141 g/d. When using the level >= 400 g/d as a cut-off, only 23.5% (13.8-37.0%) of the studied children, depending on country and gender, met the WHO recommendation (fruit juice excluded). Conclusions: Fruit and vegetable consumption was below recommended levels among the schoolchildren in all countries and vegetable intake was lower than fruit intake. The survey shows that there is a need for promotional activities to improve fruit and vegetable consumption in this age group.